Characterization of Aromatic Hydrocarbons in Tropical Coastal Water of Sabah, Borneo - Vani Annammala, Kogila; Harun Abdullah, Mohd; Bin Mokhtar, Mazlin; G. Joseph, Collin; Sakari, Mahyar (Asian Journal of Chemistry, 2013)
The presence of carcinogenic compounds in the coastal waters was monitored to assess the health effects to human and the marine environment. The details on the level of hydrocarbon contamination in the coastal waters of some small islands and the port in Kota Kinabalu were provided to initiate the management and monitoring plan for ecosystem management and restoration of the target places. This paper reports the occurrences of oil and grease and 16 USEPA listed polyaromatic hydrocarbons in the selected locations of coastal waters of Sabah. A baseline reading on the oil and grease level was established using partition-gravimetric method while detection for polyaromatic hydrocarbons was studied using GC-MS. The level of oil and grease tested were all above the limit set by the Malaysian interim standards (0.04 mg/L), while the level of monitored polyaromatic hydrocarbons were still within an acceptable level. Most polyaromatic hydrocarbons monitored were detected in trace amount and many compounds were found to be below the detection limit of 0.02 μg/mL. The highest concentration of total polyaromatic hydrocarbons detected was 1.16 μg/mL, which was detected in the coastal waters of Manukan Island. Pyrene, benzo (a) anthracene and chrysene were detected in trace amounts in all locations. The levels of monitored carcinogenic hydrocarbon compounds were below the detection limit. Though detected at low levels, the presence of these elements in the coastal water is a cause for concern, hence continuous monitoring is recommended. The cumulative concentration of these compounds in molluscs and fish should be initiated to determine the accumulated level and the xenobiotic effect to humans and marine fauna. The main contributor of these pollutants was identified to originate from boating and shipping related activity in the vicinity of these area.